2002
DOI: 10.1128/iai.70.11.5931-5937.2002
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Nematode Infection Ameliorates Experimental Colitis in Mice

Abstract: Epidemiological studies suggest that inflammatory bowel disease (IBD) is common in developed countriesIn the present study, we investigated the effect of polarizing the immune response toward the Th2 type, using intestinal nematode infection, on subsequent experimental colitis. Mice were infected with the intestinal nematode Trichinella spiralis and allowed to recover before colitis was induced with dinitrobenzene sulfonic acid. The mice were sacrificed postcolitis to assess colonic damage macroscopically, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
184
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 53 publications
8
184
0
1
Order By: Relevance
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…6 Experimentally, a number of helminth parasites, including the trematode Schistosoma mansoni and the nematodes Heligmosomoides polygyrus and Trichinella spiralis, prevent the onset or suppress the severity of type 1 diabetes in non-obese diabetic (NOD) mice, [12][13][14] experimental autoimmune encephalitis 15 and experimental colitis. [16][17][18] A clinical trial demonstrated that oral administration of porcine whipworm eggs improves symptoms in patients with inflammatory bowel disease. 19,20 To date, however, the exact mechanisms by which helminths protect against autoimmune diseases remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, animal models of arthritis, 22 type I diabetes, [12][13][14]21,24 Graves hyperthyroidism, 25 experimental autoimmune encephalitis 15,26 and colitis [16][17][18] have all been inhibited or ameliorated by infections with helminth parasites or parasite-derived products. In this study, we found that infection with filarial helminths also protects against autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the normal bacterial flora and or the decreased incidence of intestinal parasites including worm infections are cited as the basis for the hygiene hypothesis in IBD (Khan et al 2002;Strober et al 2007;Koloski et al 2008). Experimental evidence shows that gastrointestinal worm infections can suppress IBD in experimental animals and humans (Khan et al 2002;Strober et al 2007;Koloski et al 2008). In addition, approaches that aim to alter the types of bacteria in the gastrointestinal track including the use of probiotics to replace the existing bacteria with "good" bacteria have been successful in some circumstances (Rolfe et al 2006).…”
Section: Vitamin D and The Hygiene Hypothesismentioning
confidence: 99%